Managerial economics in a global economy - Salvatore, Dominick (Australia South-Western, 2002)
Managerial economics refers to the application of economic theory and the tools of analysis of decision science to examine how a firm can make optimal managerial decisions in the face of constraints it faces.
PART 1: Introduction
Chapter 1 : The Nature and Scope of Managerial Economics
Chapter 2: Optimization Techniques and New Management Tools

PART 2: Demand Analysis
Chapter 3: Demand Theory
Chapter 4: Demand Estimation
Chapter 5: Demand Forecasting

PART 3: Production and Cost Analysis
Chapter 6: Production Theory and Estimation
Chapter 7: Cost Theory and Estimation
Chapter 8: Linear Programming

PART 4: Market Structure and Pricing Practices
Chapter 9: Market Structure: Perfect Competition, Monopoly, and Monopolistic Competition
Chapter 10: Oligopoly and Strategic Behavior
Chapter 11: Pricing Practices

PART 5: Regulation, Risk Analysis, and Capital Budgeting 479
Chapter 12: Regulation and Antitrust: The Role of Government in the Economy
Chapter 13: Risk Analysis
Chapter 14: Long-Run Investment Decisions: Capital Budgeting
First published by Harcourt.
Includes bibliographical references and index.
Keywords: Managerial economics